2015
DOI: 10.1007/s11356-014-4031-0
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and speciation of vanadium in the rhizosphere soils of rape (Brassica juncea L.)

Abstract: The response of rape (Brassica juncea L.) to different vanadium (V) speciation in rhizosphere soils was investigated in pot experiments using an agricultural soil containing 147 mg V kg(-1) supplemented with 0-500 mg V kg(-1) of pentavalent V [V(V)] and a mining soil containing 774 mg V kg(-1). Tetravalent V [V(IV)] accounted for 76.1 and 85.9 % of total V in the untreated agricultural soil and mining soil, respectively. The proportion of both V(V) and water-extractable V increased with increasing concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 35 publications
0
14
0
2
Order By: Relevance
“…The mobile V in soils occurs mainly as V(V) and only minor amounts are present as V(IV) (Baken et al, 2012;Burke et al, 2012). Vanadate is also the most available form for plants (Tian et al, 2015). Although red mud, the fine sediment byproduct of bauxite processing, is not soil, a recent study provides insight into V mobilization from mineral solids.…”
Section: Fig 12 Solubility Of Some Vanadium Oxides As a Function Of Phmentioning
confidence: 99%
“…The mobile V in soils occurs mainly as V(V) and only minor amounts are present as V(IV) (Baken et al, 2012;Burke et al, 2012). Vanadate is also the most available form for plants (Tian et al, 2015). Although red mud, the fine sediment byproduct of bauxite processing, is not soil, a recent study provides insight into V mobilization from mineral solids.…”
Section: Fig 12 Solubility Of Some Vanadium Oxides As a Function Of Phmentioning
confidence: 99%
“…Vanadium (V) is a transition metal widely distributed in the Earth’s crust, where it may be found at a mean concentration of 20 to 120 mg kg -1 [ 1 ]; however, it has little mobility in soil, since less than 1% of the total V is extractable and leachable with water [ 2 , 3 ]. The first studies identified V as an element highly toxic to plants [ 4 ], which decreased interest in evaluating its effect on cultivated species.…”
Section: Introductionmentioning
confidence: 99%
“…V is generally not very mobile in the soil, and it has several cationic states, including V 2+ , V 3+ , V 4+ , and V 5+ ; the latter form is characterized by being a strong oxidant (Matsugo et al, 2015). V 4+ is the predominant form in the soil, which is less mobile and toxic than the pentavalent (V 5+ ) form (Tian et al, 2015). Small amounts of V stimulate plant biomass production, whereas root and leaf growth inhibition and morphological changes have been reported with high levels of this element in Ipomoea aquatica (Chen et al, 2016 (Nalewajko et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…forma se caracteriza por ser un oxidante fuerte (Matsugo et al, 2015). La forma predominante en el suelo es V 4+ , la cual es menos móvil y tóxica que la forma pentavalente (V 5+ ) (Tian et al, 2015). En plantas se ha reportado que pequeñas cantidades de V estimulan la producción de biomasa, mientras que niveles altos de este elemento inhiben el crecimiento y causan cambios morfológicos en hojas y raíz de Ipomoea aquatica (Chen et al, 2016 antocianinas (Schiavon et al, 2016).…”
Section: Introductionunclassified